Effects of High-Intensity Interval Training and Isoinertial Training on Leg Extensors Muscle Function, Structure, and Intermuscular Adipose Tissue in Older Adults - Bruseghini, Paolo; Capelli, Carlo; Calabria, Elisa; Rossi, Andrea P.; Tam, Enrico (Frontiers in Physiology, 2019)
We compared the effects of aerobic High Intensity Training (HIT) and Isoinertial Resistance Training (IRT) on the strength, mass, architecture, intermuscular adipose tissue (IMAT) quality and neuromuscular activation of the quadriceps in elderly subjects. 12 healthy men (69.3 ± 4.2 yy; 77.8 ± 10.4 kg; 1.72 ± 0.05 m) were exposed to 8 weeks of HIT (7 × 2-minute cycling repetitions at 90 % of V’O2peak, 3 times/week) and, after 4 months (detraining), to IRT (4 × 7 maximal concentric-eccentric knee extensions, 3 times/week). Before and after trainings we measured: knee extension isometric (TMVC) and dynamic (TC) maximal concentric torque, anatomical cross-sectional area (ACSA) at 25, 50, 75% of femur length, quadriceps volume (Vol), IMAT, pennation angle (θp) of the fibers from the vastus lateralis and voluntary activation (% Act). TMVC and TC were significantly larger only after IRT (P = 0.008); IRT was able to elicit a greater increase of anatomical CSA than HIT; Vol increases similarly and significantly after after HIT and IRT (P = 0.003-0.001); IMAT at 50 % of femur length decreased both after HIT and IRT (P = 0.001-0.003); physiological CSA (PCSA) was larger after IRT than before (P = 0.025); specific torque did not change throughout the study (45.5 N cm-2 ± 12.0); % Act of the quadriceps was significantly affected only by IRT (P = 0.011). HIT and IRT are both able to elicit beneficial modifications of muscular mass, architecture and quality (reducing IMAT) in elderly subjects in connection with an amelioration of strength. HIT and IRT caused a homogenous increase of ACSA and of Vol of the quadriceps. PCSA increases, but specific strength per unit of PCSA did not change. The increases of functional torque seemed to be attributed to a parallel increase of % Act and muscle hypertrophy only after IRT. Data suggest IMAT may be prominent indicator to track metabolic dependent activity and skeletal muscle quality.